2017
DOI: 10.1111/jdv.14385
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of acne vulgaris

Abstract: Acne vulgaris is a ubiquitary skin disease characterized by chronic inflammation of the pilosebaceous unit resulting from bacterial colonization of hair follicles by Propionibacterium acnes, androgen-induced increased sebum production, altered keratinization and inflammation. Here, we review our current understanding of the genetic architecture of this intriguing disease. We analysed genomewide association studies (GWAS) and candidate genes studies for acne vulgaris. Moreover, we included GWAS studies for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 171 publications
0
37
0
4
Order By: Relevance
“…It has long been recognized from family and twin studies that acne vulgaris has a strong hereditary component . Family‐based case–control studies have highlighted that affected first‐degree relatives are a major risk factor for developing the disorder .…”
Section: Family and Twin‐based Studiesmentioning
confidence: 99%
“…It has long been recognized from family and twin studies that acne vulgaris has a strong hereditary component . Family‐based case–control studies have highlighted that affected first‐degree relatives are a major risk factor for developing the disorder .…”
Section: Family and Twin‐based Studiesmentioning
confidence: 99%
“…Genetic factors are considered to be important in acne pathogenesis as family history of severe acne is detected in some patients with severe acne . Polymorphisms of genes encoding important cytokines playing key roles in acne pathogenesis attract attention of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The heritability of acne was proposed via multiple twins and family studies. Several genetic studies suggested the association of acne vulgaris with different gene polymorphisms and genotype distributions . The complex genetic architecture necessitates further studies in different populations to elucidate the genetic basis of acne vulgaris.…”
Section: Introductionmentioning
confidence: 99%